2010
DOI: 10.1590/s1413-86702010000500001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus: molecular and epidemiological evidence of male-to-female transmission

Abstract: Introduction:There is general consensus that hepatitis C virus is effi ciently transmitted by the parenteral route, whereas data on viral transmission by sexual or non-sexual intrafamilial contact are confl icting. Objective and Method: The aim of this study was to investigate the transmission of hepatitis C virus in nine heterosexual couples. Result: The mean age of the couples was 43.7 years. When interviewed, all of the women denied the presence of risk factors for acquisition of the infection, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…More recent studies have found evidence of spousal transmission of HCV in endemic areas [5, 6, 11, 13, 2830]. Genotypic studies provide further evidence of the spousal transmission of HCV [8, 15, 30, 31]. …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More recent studies have found evidence of spousal transmission of HCV in endemic areas [5, 6, 11, 13, 2830]. Genotypic studies provide further evidence of the spousal transmission of HCV [8, 15, 30, 31]. …”
Section: Discussionmentioning
confidence: 97%
“…This elevated risk of incident of HCV of family members could be due to sharing of implements such as razors or toothbrushes or due to sexual transmission between family members [14, 15]. Alternatively, the elevated risk may be due to shared risk factors (such as the family members all attending a particular health practitioner) rather than being caused by direct transmission between family members [13].…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation that a horizontal transmission event has occurred could be demonstrated by a high homology between the respective HCV genomes. Nevertheless, few of the previous studies included phylogenetic analysis [ 48 51 ] and sequence comparison was done only on the consensus sequence level [ 5 , 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo realizado por Cavalheiro et al (2009), através da análise filogenética da região não estrutural 5B do vírus da hepatite C entre 24 casais infectados pelo HCV, mostrou alto grau de similaridade do genoma do vírus da hepatite C, dando suporte à hipótese de transmissão entre esses casais. Cavalheiro et al (2010) afirma que o contato intrafamiliar também é um importante fator na transmissão do HCV.…”
Section: Transmissãounclassified